Exámen microscópico del bálsamo de tolú, bálsamo patológico obtenido del myroxylon toluifera H.B.K. - Maldonado, Angel (1920)
We have observed that when the preparation is done with gentle heat, crystals are cinnamic acid, naturally formed, consisting of incomplete and uncharacteristic thick prisms.